Manajemen Evaluasi Blended Learning Dalam Pembelajaran PAK SMP 14 Februari Buntong (Jurnal Manajemen Pendidikan Kristen, 2021)
ABSTRACT. The aims of the study is to obtain the results of the analysis and description of (1) the adjustment of PAK learning tools with the blended learning model; (2) suitability of teacher qualifications, learning facilities with blended learning models; (3) the process of planning and implementing PAK learning; and (4) the achievement of the learning process by using the blended learning model. The CIPP evaluation model (Context, Input, Process, Product) is the approach used in the research entitled Evaluation Management of Blended Learning in PAK Learning at SMP 14 February Buntong. Data collection in this study was carried out by means of observation, interviews, and documentation studies. Data processing is carried out with a data reduction flow where the data obtained is centered, simplified, and transformed into organized data for further conclusions. Based on the results of data processing, it was found that (1) teachers had adapted the learning tools to the use of blended learning models in PAK learning, especially in the components of the Learning Program, Learning Implementation Plan (RPP), and Minimum Completeness Criteria (KKM); (2) as a graduate of Christian religious education teacher, the PAK teacher at SMP 14 February Buntong has the competence and qualifications of a PAK educator, but still lacks of the ability to explore mobile learning which is more attractive to students. The standard is low because of the absence of PAK e-books and the absence of textbooks for students studying offline; (3) learning planning is said to be good because it has adjusted the learning content with the blended learning model, but it would be better if the implementation was maximized by teachers and students by exploring IT skills and willingness to learn; (4) cognitively, the results of the student's assessment as a whole reach the standard of assessment in the KKM but are not contradictory, and the affective measurement of students must involve parents to provide an assessment that the teacher cannot measure when face-to-face learning is not carried out. Blended learning as model learning is highly recommended to be resumed by taking into account several shortcomings that must be corrected for the achievement of maximum educational goals